DEPLOYING FINANCIAL SLACK AS A DYNAMIC CAPABILITY: MECHANISMS OF MSME RESILIENCE - Mohammad Yunies Edward (Generate Digital Publishing, 2025)
Objective: This study analyzes how the initial volume of financial slack dictates the dynamic capabilities (sensing, seizing, transforming) of SME owner-managers during severe macroeconomic crises, and explores the mechanisms by which liquidity is converted into organizational resilience. Research Design & Methods: Using a qualitative, exploratory-inductive multi-case study design, this research examines six SMEs divided into two polar clusters: high versus low financial slack. Data were collected through the triangulation of in-depth interviews, cash flow statements, and observations, and were rigorously analyzed using Gioia’s methodology via a three-stage coding process. Findings: A cross-case analysis reveals radical divergences in behavior. In the sensing phase, high slack frees up cognitive bandwidth for long-term market scanning, while cash scarcity triggers liquidity myopia that limits attention to short-term threats. In the seizing phase, resource-rich firms employ ambidextrous allocation (balanced defensive-offensive), whereas resource-poor firms experience pure defensive structural paralysis. In the transforming phase, residual capital functions as an error-tolerance cushion enveloping pivot transition risks, while cash-deficient cases are trapped in the inertia of outdated routines. Implications & Recommendations: Theoretically, this study integrates the Dynamic Capabilities Perspective and Resource Orchestration Theory by demonstrating that liquid capital is a material prerequisite for cognitive flexibility. Managerially, SME owners should avoid hyper-lean operations and treat financial slack as a strategic investment that safeguards adaptive capacity. Contribution & Value Added: This study unpacks the microfoundations of SME resilience by demonstrating that financial slack is not merely a passive asset buffer, but a vital cognitive and material catalyst that transforms strategic awareness into structured organizational renewal.